Retos de internacionalización en la pyme colombiana (2017)
The SMEs in Colombia have a large participation in the country’s economy, which proves to have a great growing potential, as well as has a wide variety of manufactured products, but unfortunately these companies are faced with barriers that do not allow its internationalization process to be successful, so they fail in the attempt. This article has the objective to determinate those factors that prevent the internationalization process, describe the challenges that face Colombia in terms of competitiveness, innovation and logistic in the colombian SMEs. The methodology used for this was the documentary review in the database and the bibliographic references. As a conclusion, it attempts to explain and help the SMEs to get into the use of tools that allow them to have a successfull internationalization process of their products or services